Pengaruh Penggunaan Base Isolator System Terhadap Respons Struktur Bangunan Dengan Analisis Time History (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Indonesia is prone to seismic hazard load due to its location situated on a meeting point of four tectonic plates. Therefore design of the building is necessary to include the earthquake load in order to minimize the damage of the buildings and also to avoid casualties resulted from collapsed structures. Several methods had been developed to eliminate the risk affected by the earthquakeload to the buildings. One of them is the use of seismic isolator. This research aimed to identify the responses of the building structure with and without base isolator. Responses of the structure were gained from time history analysis using finite element software conducted on the 25-storeyreinforced concrete building. The selected building was located in an area with high earthquake load intensity on sumatra island namely Banda Aceh, Padang and Bengkulu and constructed onlayer of soil with moderate condition. At one of the building analyzed in this research was provided with high damping rubber bearing (HDRB) base isolator. This base isolator was modeled as link element. This element connected the foundation and the upper structure. Then the building was loaded with the Cape Mendocino earthquake loads that were modified and adjusted to complywith SNI 03-1726-2012 building code. The results showed that the reduction of the velocity and acceleration of the building with HDRB ranged from 50% - 52% and 22% - 23,5%, respectively,compared to that of the building without HDRB. Thus the study is expected useful for engineers of high rise buildings in planning a stable structure in receiving earthquake loading.Thus the studyis expected useful for designers of high rise buildings in planning a stable structure in receiving earthquake loading.Keywords: base isolator, earthquake load, high damping rubber bearing, structure responses, time history analysis.